Evaluasi dan Peningkatan Kinerja Instalasi Pengolahan Air Limbah (IPAL) Komunal di Kota Banjarbaru - Rasani, Elna; Abdi, Chairul; Khair, Riza Miftahul (Jernih: Jurnal Tugas Akhir Mahasiswa, 2025)
Since the communal WWTP of Banjarbaru was operated in 2012, no evaluation has been conducted to assess the performance of the communal WWTP. The evaluation was conducted to determine the ability of the WWTP and to analyze various problems that caused the wastewater to not meet the quality standards from a technical and non-technical perspective. The methods used in this study were observation, literature study, laboratory tests, interviews, and questionnaires. Sampling locations are at the communal WWTP inlet and outlet. The results of the questionnaire were processed by scoring using a Likert scale. The results showed that the performance of communal WWTP in Banjarbaru based on technical aspects was classified into category A (good), operational and maintenance aspects, as well as financial aspects, were included in category B (good enough), and institutional aspects were included in category C (not good). Based on the results of the assessment, it is known that the performance of the Banjarbaru communal WWTP is not optimal and needs to be improved in several aspects.